Performance of serological tests available in Brazil for the diagnosis of human visceral leishmaniasis. - Mariana Lourenço Freire; Tália Machado de Assis; Edward Oliveira; Daniel Moreira de Avelar; Isadora C Siqueira; Aldina Barral; Ana Rabello; Gláucia Cota (Public Library of Science (PLoS), 2019)
Background Visceral leishmaniasis (VL) is the most severe form of leishmaniasis and is potentially fatal if not diagnosed and treated. Accurate and timely diagnosis is considered one of the pillars needed for the reduction in disease-related lethality. Brazil is currently one of the three eco-epidemiological hotspots for this disease. Several serological tests are commercially available in this country for VL diagnosis, although information on the performance of these tests is fragmented and insufficient. The aim of this study was to directly compare the performance of six commercial kits: three enzyme-linked immunosorbent assays (ELISAs), two immunofluorescence antibody tests (IFATs), one immunochromatographic test (ICT), besides one ICT, currently not commercially available in Brazil and one in-house direct agglutination test (DAT-LPC), not yet marketed. Methodology/principal findings A panel of 236 stored samples from patients with clinically suspected VL, including 77 HIV-infected patients, was tested. IT-LEISH and DAT-LPC showed the highest accuracy rate among the non-HIV-infected patients, 96.2% [CI95%: 92.8-99.7%] and 95.6% [CI95%: 91.9-99.3%], respectively. For the ELISA tests evaluated, the maximum accuracy was 91.2%, and in the inter HIV-status group analysis, no significant differences were observed. For both IFATs evaluated, the maximum accuracy was 84.3%, and a lower accuracy rate was observed among the HIV-infected patients (p = 0.039) than among the non-HIV-infected patients. The DAT-LPC was the most accurate test in the HIV-infected patients (p≤0.115). In general, no significant difference in accuracy was observed among the VL-suspected patients stratified by age. Conclusions/significance In summary, the differences in the performance of the tests available for VL in Brazil confirm the need for local studies before defining the diagnostic strategy.